Dynamic utilization of low-Altitude platforms in aerial heterogeneous cellular networks - Helmy, Mostafa; Ankaralı, Zekeriyya Esat; Siala, Mohamed; Baykaş, Tunçer; Arslan, Hüseyin (IEEE, 2017)
Aerial telecommunication platforms provide a promising solution to meet surging traffic demands as a component of future communication networks. They can be used as aerial base stations (ABSs) to build an aerial heterogeneous network architecture. In this paper, we consider a scenario where high and low altitude platforms (HAPs & LAPs) collaborate to construct such a network and analyze its performance. Firstly, we determine for each user the probability of being associated with either one of the HAP or LAP. From the association probability, the cell load of ABSs is derived. Secondly, we propose a dynamic placement and sizing algorithm for cells established by LAPs, to achieve load balancing and enhance the QoS for overall users inside the coverage of a HAP. We show, through simulation results, that the algorithm provides considerable gain over static aerial cellular networks.
Keywords: ABS; Aerial Heterogeneous Cellular Networks; HAP; LAP; Unmanned Aerial Vehicles